Auditory pathway abnormalities in Parkinson's disease - Rafaela Valiengo de Souza; Liliane Aparecida Fagundes Silva; Carla Gentile Matas (Arquivos de Neuro-Psiquiatria)
Background Parkinson's disease (PD) is a degenerative, progressive, chronic disease that mainly affects the central nervous system, caused by dopamine deficiency. One of the ways to evaluate the central nervous system is with auditory evoked potentials (AEP).